2018
DOI: 10.1002/cpt.1164
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase I Healthy Volunteer Study of UTTR1147A (IL‐22Fc): A Potential Therapy for Epithelial Injury

Abstract: Most treatments for epithelial injury target hematopoietic mechanisms, possibly causing immunosuppression. Interleukin (IL)-22 promotes tissue regeneration, acting directly on epithelial cells. UTTR1147A, a human IL-22Fc (immunoglobulin G (IgG)4) fusion protein, activates IL-22 signaling. This phase I placebo-controlled trial of single, ascending, i.v. (1-120 μg/kg) and s.c (3-120 μg/kg) doses of UTTR1147A analyzed its effects on safety, tolerability, pharmacokinetics, and pharmacodynamic biomarkers in healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 49 publications
6
48
0
1
Order By: Relevance
“…While the functional aspects of the increase in REG3A in cynomolgus monkeys given UTTR1147A were not explored in the toxicity studies reported here, systemic administration of recombinant REG3γ, a murine homologue of REG3A, partially protected against weight loss and mortality in IL22−null mice infected with Citrobacter rodentium . As with the skin findings, these transient dose‐dependent elevations in acutephase proteins as well as in REG3A were observed in human clinical trials …”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…While the functional aspects of the increase in REG3A in cynomolgus monkeys given UTTR1147A were not explored in the toxicity studies reported here, systemic administration of recombinant REG3γ, a murine homologue of REG3A, partially protected against weight loss and mortality in IL22−null mice infected with Citrobacter rodentium . As with the skin findings, these transient dose‐dependent elevations in acutephase proteins as well as in REG3A were observed in human clinical trials …”
Section: Discussionsupporting
confidence: 52%
“…5 As with the skin findings, these transient dose-dependent elevations in acutephase proteins as well as in REG3A were observed in human clinical trials. 22 Doses of 75 μg/kg and above in monkey studies presented here produced C max at or above the in vitro and in vivo EC50 level estimated from human hepatocytes (~3 μg/mL) and cynomolgus monkeys (~1 μg/mL), respectively. 19 In general, the doses of IL-22Fc required to elicit measurable serum biomarker elevations in healthy mice and monkeys (muIL-22Fc or UTTR1147A, respectively) were associated with a serum C max above 1 μg/mL and these biomarkers returned to baseline when serum levels were below the 10-100 ng/mL range.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…As no preclinical model recapitulates all aspects of human IBD, high-quality clinical data will be critical to elucidate the role of IL-22 in human disease. In one approach, an IL-22 IgG4 Fc fusion protein (UTTR1147A) was developed and shown to elicit systemic pharmacodynamic effects when administered to human volunteers (Rothenberg et al, 2019). UTTR1147A is currently being tested in patients with moderate-to-severe ulcerative colitis and Crohn’s disease (NCT03558152).…”
Section: Ibdmentioning
confidence: 99%